A highly selective two-way purification method using liquid chromatography for isolating αS2-casein from goat milk of five different breeds - Mohsin, Aliah Zannierah; Sukor, Rashidah; Selamat, Jinap; Meor Hussin, Anis Shobirin; Ismail, Intan Hakimah; Jambari, Nuzul Noorahya; Jonet, Mohd Anuar (Elsevier, 2020)
The main challenges in the purification of αS2-casein are due to the low quantity in milk and high homology with other casein subunits, i.e., αS1-casein, β-casein, and κ-casein. To overcome these challenges, the aim of this study was to develop a two-step purification to isolate native αS2-casein in goat milk from five different breeds; British Alpine, Jamnapari, Saanen, Shami, and Toggenburg. The first step of the purification was executed by anion-exchange chromatography under optimal elution conditions followed by size exclusion chromatography. Tryptic peptides from in-gel digestion of purified αS2-casein were sequenced and analyzed by LC-ESI-MS/MS. From 1.05 g of whole casein, the highest yield of αS2-casein (6.7 mg/mL) was obtained from Jamnapari and the lowest yield (2.2 mg/mL) was from Saanen. A single band of pure αS2-casein was observed on SDS-PAGE for all breeds. The αS2-casein showed coverage percentage of amino acid sequence from 76.68 to 92.83%. The two-step purification process developed herein was successfully applied for isolating native αS2-casein from goat milk with high purity, which will allow for future in vitro studies to be conducted on this protein.